PENGARUH DUKUNGAN KELUARGA DAN DUKUNGAN SEJAWAT TERHADAP KEYAKINAN DIRI PASIEN DAN MOTIVASI PASIEN PASCA STROKE DI RSUD PAMBALAH BATUNG AMUNTAI KABUPATEN HULU SUNGAI UTARA: Indonesia - ASERAN - (KINDAI, 2023)
This study aims to find out partially how much influence family support and peer support have on patient self-confidence and post-stroke patient motivation at Pambalah Batung Amuntai Hospital, Hulu Sungai Utara District, both directly and indirectly. The method used in this study is a quantitative method and with a population of 96 (ninety six) people, a total sampling technique of 96 (ninety six) people is taken, the research instrument is tested for validity and reliability testing, the data is tested using partial regression analysis (Partial Least Square/PLS) to test the five hypotheses proposed in this study. Each hypothesis will be analyzed using SmartPLS 3.0 software to test the relationship between variables. The results of this study indicate that there is a significant effect of the influence of family support and peer support on patients' self-confidence and there is an effect of family support, peer support and patient self-confidence on the motivation of post-stroke patients in Pambalah Hospital, Batung Amuntai, Hulu Sungai Utara District, the influence of family support and support. Colleagues indirectly have a significant effect on patient motivation through self-confidence. Keywords: Family Support, Peer Support, Self Confidence, Patient Motivation